A METHODOLOGICAL APPROACH TO THE INVESTIGATION OF LANGUAGE FLEXIBILITY IN PRESCHOOLERS: THE ROLE OF TOYS AND PARENTAL BELIEFS - MARIAN, Alexandra; IONESCU, Thea; BENGA, Oana (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2021)
The aim of the present study was to investigate the influence of the toy-type and parental beliefs about play in the development and use of language in a flexible manner by preschool children. Namely, we defined language flexibility as the ability to use multiple labels for the same object, in response to a particular verbal context. Children’s language flexibility was evaluated with a newly-designed task that comprised several story-like situations in which the main character needed the child’s help to solve a problem. The main results failed to prove a statistically significant difference between the two groups of children in the language flexibility task. But the performance on the language flexibility task was positively and significantly associated with some free time activities that children are frequently involved in and with parent’s willingness to let their children play with a toy in a different way than its prescribed mode. In contrast, the frequency and time spent by the child watching TV or playing on the computer was negatively and significantly associated with the performance on the language flexibility task.As a conclusion, we discussed the current results side by side with some proposals regarding both methodological improvements on the current experimental procedure and future research attempts at investigating language development and language flexibility of preschoolers.